2015
DOI: 10.7314/apjcp.2015.16.2.723
|View full text |Cite
|
Sign up to set email alerts
|

Symptom Experiences and Coping Strategies among Multi-ethnic Solid Tumor Patients Undergoing Chemotherapy in Malaysia

Abstract: Background: This study was performed to assess patient symptoms prevalence, frequency and severity, as well as distress and coping strategies used, and to identify the relationships between coping strategies and psychological and physical symptoms distress and demographic data of cancer patients. This cross-sectional descriptive study involved a total of 268 cancer patients with various types of cancer and chemotherapy identified in the oncology unit of an urban tertiary hospital. Materials and Methods: Data w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
11
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 34 publications
7
11
1
1
Order By: Relevance
“…Gender was noted as a significant predictor of problem-focused coping. These findings correspond to those of a previous study [29] and support that gender is a factor that influences the coping strategy adopted by cancer patients. However, our finding contradicts other studies that found that men are more likely to choose problem-focused coping, and women are more likely to choose emotion-focused coping [30,31].…”
Section: Discussionsupporting
confidence: 91%
“…Gender was noted as a significant predictor of problem-focused coping. These findings correspond to those of a previous study [29] and support that gender is a factor that influences the coping strategy adopted by cancer patients. However, our finding contradicts other studies that found that men are more likely to choose problem-focused coping, and women are more likely to choose emotion-focused coping [30,31].…”
Section: Discussionsupporting
confidence: 91%
“…The less common strategies used was "Substance use". The finding was similar with the study finding of Yahaya et al 13 that showed the most common used coping strategies were "Religion", followed by "Acceptance", "Use of emotional support" and "Use of instrumental support" and least common strategies used were "Behavioral disengagement", "Denial", "Self-blame" and "Substance use".…”
Section: Discussionsupporting
confidence: 90%
“…12 Brief Cope Reliability, Cronbach's alpha: 0.789. 13 The research instrument content validity was set by research advisor, subject expert and linguistic professionals.…”
Section: Methodsmentioning
confidence: 99%
“…DOI: 10.9790/0853-1708031620 www.iosrjournals.org 19 | Page chemotherapy. 13 In line with the research Saniah and Zainal, found that breast cancer patients who undergoing chemotherapy strategy EFC of highwill experience psychological distress. 14 According to Lazarus in Potter and Perry, states that the individual coping strategies are determined by the type of stress experienced by the individual, the individual life goals, beliefs about yourself and the world, and the personal resources of the individual.…”
Section: Relationship Of Family Support and Coping Strategies With Anmentioning
confidence: 57%